Pemulsaan dan Ameliorasi Tanah Salin untuk Pertumbuhan dan Hasil Kedelai - Purwaningrahayu, Runik Dyah; Taufiq, dan Abdullah (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
Most salt-affected agricultural land has low productivity such that suitable management is required to improve the productivity. Negative effect of salinity stress can be reduced by growing salt-tolerant cultivars and soil amelioration. The objective of the research was to identify effective ameliorant and effect of mulching in improving soybean growth and yield on saline soil. The research was conducted on saline soil in Lamongan District that has electrical conductivity (EC) of  11.39 dS m-1 during dry season 2016. Treatments consists of two factors that were arranged in split plot design, and replicated three times. The main plot was mulching, i.e. without mulching and mulching with 3.5 ton ha-1 rice straw. The subplots were six amelioration traits, namely without amelioration (control), 120 kg ha-1 K2O, 750 kg ha-1 S, 5 ton ha-1 gypsum, 5 ton ha-1 manure and combination of 5 ton ha-1 manure+1.5 ton ha-1 gypsum. The soybean seed used was K-13, a saline tolerant genotipe. The results showed that mulching reduced soil EC, increased K and Ca absorption, leaf chlorophyll index, improved growth and yield. Soil amelioration with K2O, sulphur, gypsum, or combination of manure+gypsum decreased soil EC and soil pH.  Amelioration with gypsum increased the grain yield of 36.3%.